rGO/Silk Fibroin-Modified Nanofibrous Patches Prevent Ventricular Remodeling via Yap/Taz-TGFβ1/Smads Signaling After Myocardial Infarction in Rats - Feng, Yanjing; Zhao, Guoxu; Xu, Min; Xing, Xin; Yang, Lijun; Ma, Yao; Qi, Mengyao; Zhang, Xiaohui; Gao, Dengfeng (Frontiers in Cardiovascular Medicine, 2021)
Objective: After acute myocardial infarction (AMI), the loss of cardiomyocytes and dysregulation of extracellular matrix homeostasis results in impaired cardiac function and eventually heart failure. Cardiac patches have emerged as a potential therapeutic strategy for AMI. In this study, we fabricated and produced reduced graphene oxide (rGO)/silk fibroin-modified nanofibrous biomaterials as a cardiac patch to repair rat heart tissue after AMI and investigated the potential role of rGO/silk patch on reducing myocardial fibrosis and improving cardiac function in the infarcted rats. Method: rGO/silk nanofibrous biomaterial was prepared by electrospinning and vacuum filtration. A rat model of AMI was used to investigate the ability of patches with rGO/silk to repair the injured heart in vivo. Echocardiography and stress–strain analysis of the left ventricular papillary muscles was used to assess the cardiac function and mechanical property of injured hearts treated with this cardiac patch. Masson's trichrome staining and immunohistochemical staining for Col1A1 was used to observe the degree of myocardial fibrosis at 28 days after patch implantation. The potential direct mechanism of the new patch to reduce myocardial fibrosis was explored in vitro and in vivo. Results: Both echocardiography and histopathological staining demonstrated improved cardiac systolic function and ventricular remodeling after implantation of the rGO/silk patch. Additionally, cardiac fibrosis and myocardial stiffness of the infarcted area were improved with rGO/silk. On RNA-sequencing, the gene expression of matrix-regulated genes was altered in cardiofibroblasts treated with rGO. Western blot analysis revealed decreased expression of the Yap/Taz-TGFβ1/Smads signaling pathway in heart tissue of the rGO/silk patch group as compared with controls. Furthermore, the rGO directly effect on Col I and Col III expression and Yap/Taz-TGFβ1/Smads signaling was confirmed in isolated cardiofibroblasts in vitro. Conclusion: This study suggested that rGO/silk improved cardiac function and reduced cardiac fibrosis in heart tissue after AMI. The mechanism of the anti-fibrosis effect may involve a direct regulation of rGO on Yap/Taz-TGFβ1/Smads signaling in cardiofibroblasts.